Importance of left atrial size in predicting adverse clinical events in hypertrophic cardiomyopathy [Hipertrofik kardiyomiyopatide olumsuz klinik olaylari öngörmede sol atriyum boyutunun önemi] - (:unkn) unknown (My University, 2008)
Objectives: This study sought to investigate the role of left atrial diameter in predicting adverse clinical events in patients with hypertrophic cardiomyopathy (HCM). Study design: The study prospectively included 83 consecutive patients (45 males, 38 females; mean age 47±17 years) with HCM. Admission transthoracic echocardiograms were obtained. Left atrial diameter was measured at end-systole from the parasternal long-axis view and left atrial diameter index (LADI) was derived (left atrial diameter/body surface area). Clinical endpoints were defined as cardiovascular death and/or worsening heart failure symptoms. The mean follow-up period was 622±366 days (range 14 to 1142 days). Results: Adverse clinical events were seen in 27 patients (32.5%), including two deaths and deterioration in NYHA functional class (n=25). Based on the median LADI of 2.5 cm/m 2, patients whose LADI was ≥2.5 cm/m 2 had a higher value of log NT-proBNP, increased maximal wall thickness, and higher rates of adverse events, advanced NYHA functional class, significant mitral regurgitation, and left ventricular outflow tract obstruction. In ROC analysis, the cutoff value of 2.2 cm/m 2 for LADI predicted adverse events with 89% sensitivity, 34% specificity, 84% negative and 38% positive predictive values. Kaplan-Meier analysis showed that patients with LADI <2.2 cm/m 2 had a significantly lower rate of adverse events. In binary logistic regression, predictors of increased LADI were female sex, advanced NYHA functional class, log NT-proBNP, maximal wall thickness, significant mitral regurgitation, and left ventricular outflow tract obstruction. However, log NT-proBNP was the only independent predictor of increased LADI in multivariate regression analysis (OR= 2.1; 95% CI: 1.3-3.4; p=0.004). Conclusion: Our data suggest that LADI may be used as a powerful predictor of adverse clinical events in patients with HCM.
Keywords: Atrial function, left; Cardiomyopathy, hypertrophic; Echocardiography; Heart atria; Prognosis; Risk factors